(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2025)
This study aims to develop fable animated video teaching materials in Indonesian Language subjects for strengthening character education in elementary school children. This study employs a qualitative method through a systematic literature review, utilizing journals and books that meet inclusion and exclusion criteria as sources. Data collection was carried out by searching keywords such as “animated video learning,” “fable learning materials,” and “character education in elementary school”. The analysis results indicate that teaching materials play a central role in learning, and the development of engaging teaching materials like "Fable Animated Video" can strengthen students’ personalities, especially at the elementary school level. A fable is a story about the lives of animals behaving like humans, containing moral messages rich in life values. The use of fable animated videos allows students not only to understand the story’s form but also to grasp the moral messages within, which can serve as examples in social life. Educators can use fable animated videos, for instance, to deliver material and explain the positive and negative impacts of the characters’ behaviors, thereby indirectly fostering good character in students. Character values that can be explored include religion, honesty, hard work, discipline, responsibility, patriotism, respecting the environment, and a strong social spirit